I'M AWARE OF MY GOAL ORIENTATION, MY FEAR OF FAILURE WILL DECREASE!: THE EFFECT OF LEARNING AWARENESS RELATED TO GOAL ORIENTATION ON FEAR OF FAILURE - Helga Graciani Hidajat; Resi Shaumia Ratu Eka Permata; Retno Sulistiyaningsih; Flavia Aurelia Hidajat (JURNAL NALAR PENDIDIKAN, 2023)
The problem that still occurs today is the fear of failure among students. This research aims to examine the effect of learning awareness related to goal orientation on fear of failure. This research method uses quantitative research with structural equation modeling (SEM) analysis to test the effect of learning awareness related to goal orientation on fear of failure. The subjects of this research were 408 students in Indonesia. This research instrument uses a modified goal orientation scale to measure learning awareness related to goal orientation and a modified achievement anxiety scale to measure fear of failure related to achievement anxiety. This research instrument was declared valid and reliable. The results of this research show that awareness of goal orientation will reduce fear of failure. Awareness of goal orientation can reduce fear of failure because students who have an awareness of goals make goals the main focus in the learning process; monitoring and evaluating the process of academic and learning failure; and encourage to determine the path to achieving goals.